2011
DOI: 10.4317/medoral.16.e149
|View full text |Cite
|
Sign up to set email alerts
|

Detection of AA-type amyloid protein in labial salivary glands

Abstract: Objectives: Among the diverse forms of amyloidosis, secondary type is the most frequent one. Diagnosis of amyloid deposition is based on the identification of the fibrillary protein amyloid by means of Congo Red (CR) or crystal violet (CV) stains, but these techniques do not differentiate between the different types of amyloid fibrils. The aim of this study was to identify by immunofluorescence (IF) AA amyloid a pathological fibrillar low-molecularweight protein formed by cleavage of serum amyloid A (SAA) prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Moreover, deposits may not be present in tissue biopsies from compromised organs like kidney and salivary glands [ 15 ]. All these may explain low sensitivity of MSGB found in our study compared to other studies that report 83 to 100% sensitivity [ 2 , 9 , 16 ].…”
Section: Discussioncontrasting
confidence: 79%
“…Moreover, deposits may not be present in tissue biopsies from compromised organs like kidney and salivary glands [ 15 ]. All these may explain low sensitivity of MSGB found in our study compared to other studies that report 83 to 100% sensitivity [ 2 , 9 , 16 ].…”
Section: Discussioncontrasting
confidence: 79%
“…In particular, LSG biopsy is less invasive and cheaper than examination of rectal mucosa. In the last years, various studies have demonstrated the utility of LSG biopsy for the detection of amyloid with correlation to secondary systemic amyloidosis [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, clinically uninvolved oral tissues have been advocated as an adjunctive or alternate biopsy site . Labial salivary gland is considered to be a safe and reliable biopsy site for diagnosing the disease …”
Section: Discussionmentioning
confidence: 99%